PERANCANGAN INOVASI MODEL BISNIS PT RIMBA PARTIKEL INDONESIA - David Christian Djunarko (Agora, 2017)
This study aims to find out the design of business model innovation suitable for PT Rimba Partikel Indonesia. This study uses a qualitative approach that obtains primary data through interviews. Informants used as many as 6 people selected by using purposive sampling technique. Test the validity of data by using triangulation test. Data analysis technique used is interactive data model analysis consisting of condensation data, display data, and conclusion. The results in this study indicate that the proposed implementation of a new business model appropriate for PT. Rimba Partikel Indonesia can pay attention to value propositions that add value to customers on JIS (Japanese Industrial Standard) certificate products. Then to improve business strategy, PT. Rimba Partikel Indonesia can expand its existing market share through customer segments elements that can achieve wider market segmentation by adding other customers to reputable furniture companies.